D'une pratique à contre-temps à une activité à contre-espace. Une interprétation géographique de l'emergence du wild-boaring en Pyrénées françaises - Suchet, André (Geographicalia, 2014)
The practice of canyoning represents an important part of mountain tourism in the Pyrenees, as well as in France and in Spain. After studying demographically different modalities of canyoning ins outhern France, it is apparent that a number of individuals descend canyons “in the evening”, including “after work”. This is especially in order to avoid tourist groups with their guide. As a result, a second study in Canigou in the French Pyrenees reveals within these groups, the emergence of a specific activity under the name of wild-boaring. The wild-boaring involves crowding down, bushy and relatively uninteresting canyons as usual criteria of canyoning.This transformation marks, we believe, the passage of a practical counter-time into counter-space activity. This aspect displays an exacerbation of a new form of rejection of the economic system in commercial outdoor recreation and of a particular form of social relationship to space. The paper also discusses the possibility of couter-places produced by the activity, but this hypothesis is not validated.
Keywords: canyoning; wild-boaring; Pyrenees; counter-time; counterspace; mountain tourism.